2019
DOI: 10.12659/msm.916185
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anemia and Postoperative Mortality in Patients with Aortic Stenosis Treated with Transcatheter Aortic Valve Implantation (TAVI): A Systematic Review and Meta-Analysis

Abstract: Departmental sources Background: Patients with severe aortic stenosis who have comorbidities that prevent general anesthesia and open cardiothoracic surgery are candidates for transcatheter aortic valve implantation (TAVI). However, TAVI can result in patient mortality following the procedure. This systematic review of the literature and meta-analysis aimed to determine the relationship between preoperative anemia and postoperative mortality in patients following TAVI. Material/Methods: PubMed, EMBASE, the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Many reports indicate that although anemia may increase the risk of surgical complications, it has no effect on 30-day mortality. These research groups involved patients undergoing rectal cancer surgery, cardiac surgery [3,13,23,24], hepatectomy [4], singlelevel lumbar surgery [25]. Others objected to the above points, insisting that anemia is an important predictor of 30day mortality, mainly in patients undergoing cardiovascular surgery [5][6][7]12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports indicate that although anemia may increase the risk of surgical complications, it has no effect on 30-day mortality. These research groups involved patients undergoing rectal cancer surgery, cardiac surgery [3,13,23,24], hepatectomy [4], singlelevel lumbar surgery [25]. Others objected to the above points, insisting that anemia is an important predictor of 30day mortality, mainly in patients undergoing cardiovascular surgery [5][6][7]12].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy of the relationship between anemia and perioperative prognosis, such as postoperative 30day mortality. It has been reported that the relationship between them is no statistically significant in patients undergoing rectal cancer surgery [2], cardiac surgery [3], hepatectomy [4], single-level lumbar surgery [4]. And conversely, some studies pointing out that anemia is an important predictor of 30day mortality in the patients undergoing, cardiovascular [5][6][7], spine tumors [8], major abdominal [9] , joint arthroplasty [10], gastrointestinal surgery [11], vascular surgery [12], and thyroidectomy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports indicate that although anemia may increase the risk of surgical complications, it has no effect on 30-day mortality. These research groups involved patients undergoing rectal cancer surgery, cardiac surgery [3,13,23,24] , hepatectomy [4] , single-level lumbar surgery [25] . Others objected to the above points, insisting that anemia is an important predictor of 30day mortality, mainly in patients undergoing cardiovascular surgery [5][6][7]12] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the relationship between them is no statistically significant in patients undergoing rectal cancer surgery [2] , cardiac surgery [3] , hepatectomy [4] , single-level lumbar surgery [4] . And conversely, some studies pointing out that anemia is an important predictor of 30day mortality in the patients undergoing, cardiovascular [5][6][7] , spine tumors [8] , major abdominal [9] , joint arthroplasty [10] , gastrointestinal surgery [11] , vascular surgery [12] , and thyroidectomy [13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is controversy of the relationship between anemia and postoperative 30 day mortality. It has been reported that the relationship between them is no statistically significant in patients undergoing rectal cancer surgery [2], cardiac surgery [3], hepatectomy [4], single-level lumbar surgery [5]. And conversely, some studies pointing out that anemia is an important predictor of postoperative 30 day mortality in the patients undergoing, cardiovascular [6] [7][8], spine tumors [9], major abdominal [10], joint arthroplasty [11], gastrointestinal surgery [12], vascular surgery [13], and thyroidectomy [14].…”
Section: Introductionmentioning
confidence: 99%